2010
DOI: 10.3390/toxins2102359
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Impact of Prokaryotic Toxins on Aquatic Environments: A Review

Abstract: Microorganisms are ubiquitous in all habitats and are recognized by their metabolic versatility and ability to produce many bioactive compounds, including toxins. Some of the most common toxins present in water are produced by several cyanobacterial species. As a result, their blooms create major threats to animal and human health, tourism, recreation and aquaculture. Quite a few cyanobacterial toxins have been described, including hepatotoxins, neurotoxins, cytotoxins and dermatotoxins. These toxins are secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
1
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(70 citation statements)
references
References 238 publications
(305 reference statements)
2
62
1
5
Order By: Relevance
“…Cyanobacteria are one of the most important groups of toxin-producing aquatic bacteria. Species within the cyanobacterial genera identified in this study have been reported to produce various secondary metabolites, including microcystins, cytotoxins, and neurotoxins (52). Cyanobacterial populations have also been detected in 16S rRNA gene clone libraries of chlorine-treated DW (37).…”
Section: Resultsmentioning
confidence: 74%
“…Cyanobacteria are one of the most important groups of toxin-producing aquatic bacteria. Species within the cyanobacterial genera identified in this study have been reported to produce various secondary metabolites, including microcystins, cytotoxins, and neurotoxins (52). Cyanobacterial populations have also been detected in 16S rRNA gene clone libraries of chlorine-treated DW (37).…”
Section: Resultsmentioning
confidence: 74%
“…Cyanotoxins detected and correspondent taxa from which have been isolated, as well as their primary target in mammals. Based on the information from Chorus et al, 2000;Charmichael, 2001;Codd et al, 2005;Stewart et al, 2006;van Apeldoom et al, 2007;Bláha et al, 2009;Valério et al, 2010;Mihali et al, 2009. * -the dose needed to kill 50% of exposed animals.…”
Section: Why the Surveillance On Cyanobacteria?mentioning
confidence: 99%
“…Most of cyanobacterial secondary metabolites are alkaloids, or possess peptidic substructures synthesised by NRPS (non-ribosomal peptide synthesis, involving peptide synthetases) or NRPS/PKS (involving peptide synthetases and polyketide synthases) hybrid pathways (Valério et al, 2010).…”
Section: Cyanotoxinsmentioning
confidence: 99%
“…They are characterized by cosmopolitan distribution, species diversity and ability to produce several secondary metabolites with different biological activity. It is suggested that these secondary metabolites determine the high biological adaptability and cosmopolitanism of cyanobacteria and this is a part of their strategy for survival [1].…”
Section: Introductionmentioning
confidence: 99%